Surface passivation engineering for stable optoelectronic devices via hydroxyl-free ZnMgO nanoparticles - Seongkeun Oh; Jaehwi Choi; Junhyeok Park; Young Kyun Choi; Taesung Park; Awais Ali; Junhyuk Ahn; Jiwan Kim; Soong Ju Oh (Nano Convergence)
Abstract ZnMgO nanoparticles (ZMO NPs) are widely used as electron transport layers in optoelectronic devices such as light-emitting diodes (LEDs) and photodiodes (PDs) primarily because of their facile synthesis and excellent electron transport properties. However, the surface hydroxyl groups (‒OH) on the ZMO NPs introduce charge traps, inhibit electron transport, and reduce device stability, particularly under ambient humidity and oxygen. Therefore, in this study, an alcohol treatment (AT) method was developed to remove surface ‒OH via proton transfer to effectively reduce trap states and dipole moments and enhance surface passivation. Quantum-dot-based LEDs and PDs fabricated using the AT-based ZMO NPs exhibited improved current density, luminance, and external quantum efficiency compared to the untreated devices. Notably, the methanol-treated devices achieved an operational lifetime of approximately 28 h under ambient conditions, representing a substantial advancement in device stability and performance. The AT approach is a simple and effective strategy for optimizing the ZMO NPs for next-generation optoelectronic applications.